Moderasi Kepemilikan Manajerial Terhadap Faktor-Faktor Yang Mempengaruhi Income Smoothing - Mimelientesa Irman; Linda Hetri Suriyanti; Hendra Wijaya (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
The objective of this study is to analyze of business strategy, company size and financial performance on income smoothing with managerial ownership as a moderating variable. The object of this research is the infrastructure, utility and transportation sector service companies listed on the Indonesia Stock Exchange in 2015-2019. The sampling technique used purposive sampling method and used Moderated Regression Analysis (MRA) method for The analytical. The number of samples used in this study were 32 companies. The results show that: Business strategy has no effect on income smoothing, Firm size has an effect on income smoothing, Financial performance has no effect on income smoothing, Managerial ownership is not able to moderate the effect of business strategy on income smoothing, Managerial ownership is not able to moderate the effect of firm size on income smoothing, Managerial ownership is not able to moderate the effect of financial performance on income smoothing.